The purge : anarchy [videorecording (DVD)] - Demonaco, James; Ejogo, Carmen, 1974-; Beasley, John, 1943-; Gilford, Zach, 1982-; Grillo, Frank, 1963- ([Publisher not identified], 2014)
The New Founders of America invite you to celebrate your annual right to Purge. Writer/director James DeMonaco returns to craft the next terrifying chapter of dutiful citizens preparing for their country's yearly twelve hours of anarchy.